STRATEGIES FOR MAINTAINING CUSTOMER SATISFACTION POST PRODUCT RECALL: SYNERGY OF SETTLEMENT, BRAND EQUITY, AND LEVEL OF SEVERITY - Zaenal Aripin; Ricky Agusiady; Kosasih (PT. Kreatif Indonesia Satu, 2024)
The strategy of maintaining customer satisfaction after product withdrawal is a major concern for companies in the competitive business era. This research aims to investigate how completion synergy, brand equity, and product withdrawal severity interact in the context of strategies for maintaining customer satisfaction. The main objective of this research is to understand how completion synergy, brand equity, and severity of product withdrawal influence customer satisfaction after product withdrawal. In addition, this study also aims to explore effective strategies in managing various levels of product withdrawal severity. The research method used in this research is qualitative, using data obtained from related journals, articles and books. Qualitative data will be analyzed using an inductive approach to explore various aspects of strategies for maintaining customer satisfaction after product withdrawal. The research results show that completion synergy, brand equity, and the severity of product withdrawal interact with each other and influence customer satisfaction after product withdrawal. Companies that are able to provide holistic solutions, have strong brand equity, and respond appropriately to the severity of product recalls tend to have higher levels of customer satisfaction.